2015
DOI: 10.1016/j.ajpath.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor Cell Dysfunctions Underlie Some Diabetic Complications

Abstract: Stem cells and progenitor cells are integral to tissue homeostasis and repair. They contribute to health through their ability to self-renew and commit to specialized effector cells. Recently, defects in a variety of progenitor cell populations have been described in both preclinical and human diabetes. These deficits affect multiple aspects of stem cell biology, including quiescence, renewal, and differentiation, as well as homing, cytokine production, and neovascularization, through mechanisms that are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 114 publications
1
26
0
Order By: Relevance
“…Moreover, tissue-specific progenitor cellssuch as endothelial and cardiac progenitor cellshave similar glucose uptake and HK2 expression. Their dysfunction in diabetes is likely driven by HK2-linked glycolytic overload and also contributes to the development of diabetic complications [31].…”
Section: Evidence Of Hk2-linked Glycolytic Overload In Diabetes and Imentioning
confidence: 99%
“…Moreover, tissue-specific progenitor cellssuch as endothelial and cardiac progenitor cellshave similar glucose uptake and HK2 expression. Their dysfunction in diabetes is likely driven by HK2-linked glycolytic overload and also contributes to the development of diabetic complications [31].…”
Section: Evidence Of Hk2-linked Glycolytic Overload In Diabetes and Imentioning
confidence: 99%
“…The experiments confirmed the existence of cardiac progenitor cells expressing c‐kit, sca‐1, GATA‐4, GATA‐5, Mef2C, and NKx2.5 . Various scientific experiments revealed that diabetic condition affects the dynamic cardiac c‐kit + cells (CPCs) . Considering the paracrine pro‐angiogenic capacity and transdifferentiate into endothelial‐ and pericyte‐like cells, it is believed that CPCs take part in favour of vascularization, holding great promise for restoration of different tissues during injuries .…”
Section: Introductionmentioning
confidence: 71%
“…8 Various scientific experiments revealed that diabetic condition affects the dynamic cardiac c-kit + cells (CPCs). [9][10][11][12] Considering the paracrine pro-angiogenic capacity and transdifferentiate into endothelial-and pericyte-like cells, it is believed that CPCs take part in favour of vascularization, holding great promise for restoration of different tissues during injuries. [13][14][15] The transdifferentiation into endothelial-and pericyte-like cells is initiated by expressing cell distinct markers such as vWF (Von Will brand factor), CD31 (Platelet endothelial cell adhesion molecule [PECAM-1]), NG 2 (neural/glial antigen 2), and α-SMA (alpha smooth muscle actin), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic patients in particular have reduced recruitment of stem cells to ischemic regions, circulating endothelial progenitor cells and endothelial cell function 46,47 . We examined the expression of SCF/tmSCF in skin samples from diabetic and non-diabetic patients to assess differences.…”
Section: Diabetic Patients Have Reduced Endothelial Stem Cell Factor mentioning
confidence: 99%